Colour Evaluation of Pinot Noir and Merlot Wines after Malolactic Fermentation Carried out by Oenococcus oeni and Lactobacillus plantarum Patagonian Native Strains - Olguin, N.T.; Delfederico, L.; Semorile, L. (South African Journal of Enology and Viticulture, 2020)
Malolactic fermentation is a complex process that involves many reactions aside from the decarboxylation of L-malic acid. But we still have only glimpses of that complexity. It is not clear if the phenolic composition and colour are affected by malolactic fermentation and, if so, to what extent. So, the aims of this study were: 1) to evaluate the behaviour of native Patagonian strains of Oenococcus oeni and Lactobacillus plantarum in two wine varieties, and 2) to analyse the effect of malolactic fermentation on the colour of these wines. Our results show that the survival of bacteria and L-malic acid decarboxylation is different depending on the lactic acid bacteria strain employed and the wine variety. In addition, we found that O. oeni can survive in wine even when L-malic acid is not being consumed. We found some correlations between MLF and colour-related parameters in Pinot noir but not for Merlot. In fact, some of the colour-related parameters measured in Merlot (total polyphenolic index, colour intensity, hue, as well as the CIELAB parameters) were affected even when L-malic acid was not being consumed.